Выбор конструкции электрического двигателя для бесштанговых насосов - Карпенко, Илья Николаевич; Юрьева, Елена Юрьевна (НТУ "ХПИ", 2014)
Проведен сравнительный анализ электрических двигателей вращательного и поступательного движения, приводящих в движение привод бесштангового насоса. Рассмотрены погружные асинхронные двигатели серии ПЭД, регулируемые вентильные двигатели, вентильные двигатели с постоянными магнитами, вентильные индукторные двигатели, линейные коаксиальные асинхронные и коаксиальные линейные синхронные двигатели с постоянными магнитами.

The comparative analys of electric motors rotational and translational motion that drive the actuator rodless pump was conducted. Submersible induction motors ПЭД series, adjustable valve motors, brushless motor with permanent magnets, gate inductor motors, linear induction coaxial and coaxial linear synchronous motors with permanent magnets were analysed. strengths and weaknesses of each of the proposed electric motors were identified. The requirements for electric motors that used in rodless pumps have been identified. It is concluded that the most promising coaxial lineytsnom synchronous motor with permanent magnets.
Select of Design of Electric Motor for Rodless Pumps
Keywords: асинхронные двигатели; цилиндрический линейный асинхронный двигатель; синхронный линейный коаксиальный двигатель; постоянные магниты; электромеханика; cylindrical linear induction motor; synchronous linear coaxial motor; permanent magnets; electromechanics